Pelajar Papua dalam Kuasa Simbolik (Studi Terhadap Reproduksi Kelas Sosial di SMK Negeri 1 Obaa, Mappi, Papua) - Marianus Muharli Mua (Jurnal Sosiologi Agama, 2015)
In this study shown that at SMK Negeri 1 Obaa located inMappi, Papua turns performing two roles namely the role ofproduction and reproduction of social classes. Social classreproduction occurs because internelization of habitus, culture,taste and mindset of classes conducted by both the school andthe students themselves. Through regulations and disciplineimposed by the school has established habitus students andinteraction among students as a means of hegemony students tofollow habitus, tastes, culture and mindset of the social upperclass. This school serves as a structure that perpetuates violenceand symbolic power of the lower classes. At the school becamethe battle arena and fight to maintain the existing capital ieeconomic capital, social capital, cultural capital and symboliccapital. Through mastery of existing capital, schools producingand reproducing social classes. For the lower social classes it isa production that will raise the social status while the upperclass it is a top-class reproduction and dominance. However,the impact of symbolic domination that occurred in this schoolmakes the lower class who do not have the capital to beeliminated. In addition, the school culture is the culture of thedominant class so delivers lower classes in Mappi are stilldominated by hunting and gathering are not able to adapt toschool culture into pressure and not as important in their lives.Keywords: Schools, Gaps, Reproduction, Social Class, Strategy,Attorney Symbolic